2021
DOI: 10.3390/biom11101480
|View full text |Cite
|
Sign up to set email alerts
|

Novel Xanthone Derivatives Impair Growth and Invasiveness of Colon Cancer Cells In Vitro

Abstract: Natural xanthones are a large group of compounds from which promising anticancer properties could be further developed by chemical modifications. This study aimed to investigate the influence of four novel xanthone derivatives based on a naturally occurring xanthone skeleton on the invasiveness of colon cancer cells in vitro. First, the concentrations required to inhibit growth of three colorectal cancer cell lines to 50% (GI50) of all the studied compounds, as well as the natural xanthones used as a reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Finding selective drugs with low toxicity to normal cells that are not Pgp substrates may thus be one of the ways to effectively treat this disease. Several studies concerning the evaluation of the biologic activity of xanthones demonstrated that they often present anti-tumor activity [13,[30][31][32], besides many other interesting biological activities, including anti-oxidant, anti-inflammatory, anti-allergy, anti-bacterial, anti-fungal, and anti-viral activities [12,33,34]. Some cell targets for xanthone derivatives have already been described and include, among others, cyclin dependent kinases, important in cell cycle control [35,36], cytokines, kinases that modulate the activity of PI3K, Akt, and TOR proteins or proteins involved in apoptosis, like Bax, Bcl-2, or caspase 3 [37].…”
Section: Effect Of Chiral Derivatives Of Xanthones On the Growth Of H...mentioning
confidence: 99%
“…Finding selective drugs with low toxicity to normal cells that are not Pgp substrates may thus be one of the ways to effectively treat this disease. Several studies concerning the evaluation of the biologic activity of xanthones demonstrated that they often present anti-tumor activity [13,[30][31][32], besides many other interesting biological activities, including anti-oxidant, anti-inflammatory, anti-allergy, anti-bacterial, anti-fungal, and anti-viral activities [12,33,34]. Some cell targets for xanthone derivatives have already been described and include, among others, cyclin dependent kinases, important in cell cycle control [35,36], cytokines, kinases that modulate the activity of PI3K, Akt, and TOR proteins or proteins involved in apoptosis, like Bax, Bcl-2, or caspase 3 [37].…”
Section: Effect Of Chiral Derivatives Of Xanthones On the Growth Of H...mentioning
confidence: 99%
“…During this period, under the concentration of 0.4 x 10 3 µg/mL, the inhibition rate is 92% and is balanced at 95% with increased dosage. Xanthone derivatives (gambogic acid and α-mangostin) impair colorectal cancer proliferation, motility, adhesion to extracellular matrix and to endothelial cells, and also induce apoptosis and cell death (Rech et al, 2021).…”
Section: Cytotoxicity Testmentioning
confidence: 99%
“…Tests that can associate treatments with evaluation of the synergistic effect between them provide an interesting perspective, such as, for example, cell exposure to chemotherapy for 24 hours and immediately after a second exposure of cells to the flavonoid alone or associated with it. Xanthonic derivatives (gambogic acid and α-mangostin) exhibit comparative results to the chemotherapeutic agents cisplatin and 5-fluorouracil on colon tumor cells Rech et al (2021) and doxorubicin and vinblastine on leukemia, hepatocarcinoma and breast cancer cell lines (Kuete et al, 2014).…”
Section: Cytotoxicity Testmentioning
confidence: 99%
“…Examples of synthesized CDXs with enantioselectivity that have been explored in our research group include CDXs as cell growth inhibitors [ 6 , 22 , 23 ], sciatic nerve blockers [ 24 ], antimicrobial resistance mechanism inhibitors [ 25 ], and cyclooxygenase inhibitors [ 10 ]. A great contribution in this field was also made by Professor Marona’s research team, describing a variety of CDXs with diverse activities, such as anticonvulsant [ 26 ], local anesthetic [ 26 ], cardiovascular [ 27 ], antifungal and antibacterial [ 28 ], antiarrhythmic [ 29 ], antiplatelet aggregation [ 30 ], antiadrenergic receptors [ 31 ], and more recently antioxidant [ 32 , 33 ] and anticancer potential [ 34 , 35 ]. Although the strategy to conjugate amino acids with xanthone derivatives has been explored in the screening of different biological activities, the enantioselectivity was frequently neglected [ 2 , 3 , 36 ].…”
Section: Introductionmentioning
confidence: 99%